2007
DOI: 10.1016/j.fertnstert.2007.07.150
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the efficiency of oocyte donation program using egg cryo-banking

Abstract: matured MII or IVM-MII oocytes were collected and processed rapidly. RNA was extracted and amplified using a 2-round in vitro transcription procedure, then labeled and hybridized to Applied Biosystems Human Genome Survey Microarrays. This array interrogates 29,098 genes. Up-or down-regulated genes were classified according to the molecular function, biological process, or pathway in which they participate. Statistical analysis was employed to compare each class of genes between samples.RESULTS: The in vitro tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 0 publications
6
64
0
2
Order By: Relevance
“…Nagy et al [35] performed a study in which oocytes from ten donors were cryopreserved by vitrification and subsequently thawed for transfer to a total of 20 recipients. They achieved an 87.5% survival, 87% fertilization and 68% blastocyst formation rate.…”
Section: Oocyte Cryopreservation Is Not Experimentalmentioning
confidence: 99%
See 2 more Smart Citations
“…Nagy et al [35] performed a study in which oocytes from ten donors were cryopreserved by vitrification and subsequently thawed for transfer to a total of 20 recipients. They achieved an 87.5% survival, 87% fertilization and 68% blastocyst formation rate.…”
Section: Oocyte Cryopreservation Is Not Experimentalmentioning
confidence: 99%
“…Results from series of frozen oocytes (reviewed in ref [32]) compare favorably to these data, especially when one takes into account that in many oocyte thaw studies (those performed by the Italian groups) the number of oocytes that could be thawed and inseminated was limited to three, due to federal statute. If one looks at studies using frozen donor oocytes, the data are even more favorable, with ongoing pregnancy and delivery rates exceeding 50% in some reports [29,[33][34][35]. Thus, although the source of oocytes in the latter studies is from women age <39 years, existing age-appropriate data suggests that there may be no benefit in offering embryo cryopreservation vs. OC, at least from a subsequent thaw success perspective.…”
Section: Oocyte Vs Embryo Cryopreservationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, advances in oocyte vitrification techniques have resulted in higher oocyte survival rates from the cryopreservation process. Recent studies have demonstrated equivalent clinical pregnancy rates in IVF cycles using cryopreserved oocytes and embryos [8,23]. The success of oocyte cryopreservation provides a new dimension to the fertility preservation options available for female oncology patients.…”
Section: Discussionmentioning
confidence: 99%
“…Those results have been replicated in multiple other retrospective studies [23][24][25] . Other authors have also commented on the lack of differences noted in embryo quality between fresh and frozen oocytes from the same donor 26,27 . Finally, as with embryo cryopreservation, the younger age of this patient population at oocyte retrieval would favour even better success rates.…”
Section: Oocyte Cryopreservation With Ovarian Stimulationmentioning
confidence: 99%